(untitled) (Innovative professional education, 2024)
Digital technology solutions have become essential for improving the overall practice of professional training. Integrating digital technologies to enhance personalized learning has become a standard way of supporting learners in an increasingly digital world. The introduction of SMART-complexes allows for a comprehensive approach to the problem of vocational education digitalization. It has been established that professional training of specialists using SMART-complexes is deployed at three levels between: students; students and teachers; students and content.